Analisis Kajian Kelayakan Usaha Bum Des â€œBeriuk Berkaryaâ€ Desa Lando Unit Usaha Sistem Penyediaan Air Minum Desa Serta Perannya dalam Peningkatan Pendapatan Asli Desa Tahun 2018/2019 - Aini, Qurratul; Mawardi, Mawardi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2019)
The purpose of this study was to determine the feasibility of BUM Des ?BERIUK BERKARYA? business of the stigma of the unit of the village Drinking Water Supply System both in term of Financial Aspects and Non-Financial Aspects as well as knowing how much the role in the Original Village Revenue was analyzed using Percentage Calculations. This research uses the feasibility study theory of BUM Deep business from Ibrahim in Hastowiyono and Suharyanto (2014). The method used is a qualitative method with a descriptive approach. Date collection techniques used are interviews, observation, documentation, and form. Date analysis used in this study is a non-financial feasibility analysis and a financial feasibility analysis that is measured from the investment assessment and percentage analysis. The results of the Non-Financial Feasibility analysis and feasibility of the Financial Aspect show that the village drinking water supply system business can be declared feasibility to run. While from the percentage analysis results, this business can play a role in increasing the original income of Lando village.